Applications of functionalized polyethylene terephthalate aerogels from plastic bottle waste. (December 2019) - Le, Duyen Khac; Leung, Ryan I.H.; Er, Alan S.R.; Zhang, Xiwen; Tay, Xiang J.; Thai, Quoc Ba; Phan-Thien, Nhan; Duong, Hai M.
Graphical abstract: Highlights: Modify rPET aerogel by silicone ceramic coating and (3-aminopropyl)triethoxysilane. Rigidity of aerogel structure increase up to 124.8 kPa and hydrophobicity of 144.7°. Enhanced thermal stability of up to 600 °C, thermal insulation of 31.8–34.9 mW/m·K. CO2 adsorption capacity of the rPET aerogel enhance up to 300% with 0.44 mmol CO2 /g. Abstract: Millions of tons of plastic are produced annually, but less than 10% are reported to be recycled. This work sets out to transform environmental plastic (polyethylene terephthalate – PET) waste into aerogels for high-value engineering applications, primarily to enhance the monetary incentive in recycling plastics. Coating techniques, using silicone ceramic (SCC) and (3-aminopropyl)triethoxysilane (APS, or APTES) solutions, are successfully devised to enhance the thermal stability and CO2 adsorption capability of rPET aerogel. The rPET/SCC aerogel exhibits improved thermal stability (up to 600 °C), enhanced thermal insulation (thermal conductivity Kavg = [31.8–34.9] mW/m·K), hydrophobic characteristics (up to 144.7° in contact angle) and enhanced rigidity (Young modulus Eavg = [4.5–124.8] kPa), while maintaining an ultra-low density ( ρa = [14–62] g/cm 3 ) and a high porosity ( Φavg = [95.6–99.0]%). Moreover, the amine-functionalised rPET aerogel achieves a CO2 adsorption capacity of up to 0.44 mmol CO2 /g, superior to several commercial physio-sorbents. These promising results obtained demonstrate that the rPET aerogel is a versatile material suitable for a wide variety of high-value engineering applications, including thermal insulation and direct CO2 capture applications.